Atlantia : a novel - Condie, Allyson Braithwaite. (Dutton Books, an imprint of Penguin Group (USA) LLC, 2014)
"Rio has always dreamed of leaving the underwater city of Atlantia for life in the Above; however, when her twin sister, Bay, makes an unexpected decision, Rio is left stranded below where she must find a way to unlock the secrets of the siren voice she has long hidden and save Atlantia from destruction"--